How Aggregate Volatility-of-Volatility Affects Stock Returns. (24th July 2017) - Hollstein, Fabian; Prokopczuk, Marcel
Abstract: A stylized theoretical model with stochastic volatility suggests the existence of a trade-off between returns and volatility-of-volatility. Using the VVIX, a measure of the option-implied volatility of the volatility index, we confirm this prediction and detect that time-varying aggregate volatility-of-volatility commands an economically substantial and statistically significant negative risk premium. We find that a two-standard-deviation increase in aggregate volatility-of-volatility factor loadings is associated with a decrease in average annual returns of about 11%. These results are robust to controlling for aggregate volatility, jump risk, and several other characteristics and factor sensitivities, as well as various additional tests. Received September 05, 2016; accepted June 21, 2017 by Editor Raman Uppal